Effects of STN DBS on Rigidity in Parkinson's Disease - Shapiro, Mark B.; Vaillancourt, David E.; Sturman, Molly M.; Verhagen Metman, Leo; Bakay, Roy A. E.; Corcos, Daniel M. (IEEE transactions on neural systems and rehabilitation engineering, 2007)
We quantified the effects of deep brain stimulation (DBS) of the subthalamic nucleus (STN) and medication on Parkinsonian rigidity using an objective measure of work about the elbow joint during a complete cycle of imposed 1-Hz sinusoidal oscillations. Resting and activated rigidity were analyzed in four experimental conditions: 1) off treatment; 2) on DBS; 3) on medication; and 4) on DBS plus medication. Rigidity at the elbow joint was also assessed using the Unified Parkinson's Disease Rating Scale (UPDRS). We tested ten patients who received STN DBS and ten age-matched neurologically healthy control subjects. The activated rigidity condition increased work in both Parkinson's disease (PD) patients and control subjects. In PD patients, STN DBS reduced both resting and activated rigidity as indicated by work and the UPDRS rigidity score. This is the first demonstration that STN stimulation reduces rigidity using an objective measure such as work. In contrast, the presurgery dose of antiparkinsonian medication did not significantly improve the UPDRS rigidity score and reduced work only in the activated rigidity condition. Our results suggest that STN DBS may be more effective in alleviating rigidity in the upper limb of PD patients than medications administered at presurgery dosage level.